Treatment of calcifying epithelial odontogenic tumor/Pindborg tumor by a conservative surgical method - T Vigneswaran; R Naveena (Wolters Kluwer Medknow Publications, 2015)
Calcifying epithelial odontogenic tumor (CEOT) also known as Pindborg tumor is a rare odontogenic epithelial neoplasm. So far nearly 200 cases have been reported in literature. We are reporting a case of CEOT in a 42-year-old male patient with painless bony swelling in the mandible. Approximately, 50% of the cases are associated with an unerupted tooth or odontome, but was not so with our case. Considering the intrabony mandibular location of the lesion and its limited size, we opted for a more conservative surgery. The clinical, radiographic and histopathologic features and the surgical treatment done are discussed with relevant references.